(untitled) (Research, Society and Development, 2023)
With the aim of identifying how Palliative Care practices interfere with the mental health of health professionals working as palliativists within a health institution, this study addresses the interference of Palliative Care practices in the mental health of multidisciplinary teams in the Programa de Assistência e Internação Domiciliar (PAID), in the municipality of Cascavel, in the state of Paraná. Using the quantitative and qualitative research method, this study included the perceptions of medical, nursing, nursing technician, social worker, physiotherapist and nutritionist professionals working in the home care institution. Emotional distress, feelings of helplessness and grief, principles of burnout and the consequences of the absence of a professional psychologist on the team were some of the factors observed in the research. Based on the results, there is a need to implement coping strategies and mental health care for the public, as well as the importance of psychology professionals in this field.